Automatic voltage regulation application for PV inverters in low-voltage distribution grids – A digital twin approach. (July 2023) - Gui, Yonghao; Nainar, Karthikeyan; Ciontea, Catalin-Iosif; Bendtsen, Jan D.; Iov, Florin; Shahid, Kamal; Stoustrup, Jakob
Highlights: A three-layer coordinated control strategy for PV inverters is introduced. A digital twin of the cyber-physical system for low voltage distribution system is employed. The proposed method improves the voltage quality in the grid. The proposed method manages reactive power outputs of PV inverters efficiently. Abstract: This paper proposes a hierarchical coordinated control strategy for PV inverters to keep voltages in low-voltage (LV) distribution grids within specified limits. The top layer of the proposed architecture consists of the designed automatic voltage regulation (AVR) application, which has access to voltage measurements and grid parameters from the LV distribution grid, both current and historical. The AVR application solves a constrained optimization problem, which provides a set of local control set-points that bring the voltage across the grid within bounds. The middle layer consists of a local Volt/VAR controller, which is adjusted by the AVR app, while the bottom layer is the inner-loop controller of the PV inverter. The proposed method not only improves the voltage quality in the grid but also manages the reactive power outputs of PV inverters efficiently. A digital twin of the cyber-physical system has also been employed that interacts with the control system to ensure its appropriate operation. The effectiveness of the proposed methodology is demonstrated on a representative low-voltage feeder located in Denmark.